Dynamics of homegarden structure and function in Kerala, India - A. Peyre,, A. Guidal, K.F. Wiersum and F. Bongers (Agroforestry Systems (2006) 66:101-115, 2006)
Homegardens in Kerala have long been important multi-purpose agroforestry systems that combine ecological and socioeconomical sustainability. However, traditional homegardens are subject to different conversion processes linked to socioeconomic changes. These dynamics were studied in a survey of 30 homegardens. On the basis of a cluster analysis of tree/shrub species density and subsequent further grouping using homegarden size as additional characteristic, six homegarden types were differentiated. These were assessed regarding structural, functional, management and dynamics characteristics. Four development stages of homegardens were found along a gradient from traditional to modern homegardens. Fifty percent of the homegardens still displayed traditional features, whereas 33 per cent incorporated modern practices. The process of modernisation includes a decrease of the tree/shrub diversity, a gradual concentration on a limited number of cash-crop species, an increase of ornamental plants, a gradual homogenization of homegarden structure and an increased use of external inputs. One homegarden was characterised as an adapted traditional homegarden combining multispecies composition and intensive management practices using internal inputs with commercial production. In comparison to modern homegardens, this homegarden type offers an example of an alternative development path in adapting homegardens to changing socioeconomic conditions. The study of structural and functional dynamics of homegardens offers the opportunity to understand the trends in socio-economic sustainability and how these relate to ecological sustainability.